Examining the Movement Differences in the Behavior of Normal and Rack Railway Vehicle - Nagy, Andor; Lakatos, István (International Journal of Engineering and Management Sciences, 2019)
The rack railway is a special type of railroad. There weren”t much built worldwide, and their number is decreasing. Now, in Budapest, there is a possibility to create an interoperable vehicle, based upon the experience gained from the previously operated line, and all the research regarding its unique characteristics. One from the many important sector of its operation, is the rail/rack/vehicle system. Its mechanical model is far more complex than a traditional railroad vehicle. We will demonstrate its behaviorial differences from a traditional railroad vehicle.